Pregnancy status alters IL-21-mediated effects on murine B lymphocytes. Issue 3 (March 2020) - Fröhlich, Carolin; Ehrhardt, Jens; Krüger, Diana; Trojnarska, Dominika; Zygmunt, Marek; Muzzio, Damián Oscar
Abstract : A favorable outcome of pregnancy depends greatly on an adequate balance of immune protection and fetal tolerance at the fetomaternal interface. IL-21 is a pro-inflammatory cytokine associated with altering immune responses in autoimmune diseases. IL-21 has pleiotropic functions, including induction of Th17 T cells, inhibition of Treg development, and modulation of antibody responses of B lymphocytes. Genetic polymorphisms of IL21 have been associated to poor pregnancy outcomes. However, the mechanism of IL-21 actions needs further evaluation. Here, we postulate that IL-21 affects splenic B cell function during pregnancy and shapes immune responses. We show that splenic B cells from CBA/J × BALB/c mice with favorable pregnancy outcome expressed lower IL21R levels than in CBA/J × DBA/2J mice, a mouse model for immune-induced bad pregnancy outcome. As a consequence, B cells from CBA/J × BALB/c mice reacted less sensitively to IL-21 than B cells from non-pregnant mice (NPM) or from CBA/J × DBA/2J mice. Also, LPS-induced apoptotic rates were altered in NPM and CBA/J × DBA/2J but not in CBA/J × BALB/c mice. This is accompanied by improved survival of B cells that produce the anti-inflammatory cytokine IL-10 upon stimulation with LPS. We also observed lower numbers of CD4 + CXCR5 + Bcl-6 + follicular T-helper cells (Tfh) in normal pregnant mice, compared to non-pregnant and mice with disturbed pregnancies. Our data indicate that alterations of the Tfh/IL-21/IL-10 axis may have important influence on pregnancy outcome.